Tambo Alam Minangkabau : Studi Historiografi Tradisional dalam buku Tatanan Adat Warisan Nenek Moyang Orang Minang Karya Ibrahim Dt Sanggoene Diradjo yang berjudul Peristiwa Batu Batikam - Muhammad Fajar Alfiansyah; Etmi Hardi (Jurusan Sejarah FIS UNP, 2023)
This study examines the Tambo Alam Minangkabau: The Customary Order of the Ancestors of the Minangkabau Ancestors by Ibrahim Dt Sanggoene Diradjo regarding the Batu Batikam Event. The purpose of this study is to examine a work in the tambo based on traditional historiography. This research is included in the type of historical qualitative research. Therefore the research, Tambo Alam Minangkabau: Traditional Historiographical Studies in the book Customary Orders Inherited by the Minang People's Ancestors by Ibrahim Dt Sanggoene Diradjo. in the form of articles, books or journals. The first step in this research is to collect books or writings that are relevant to the study. The second step is analysis and interpretation. Then the third step is presenting the findings or research results in the form of a report or historiography